2017
DOI: 10.3390/ijms18112355
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Damage Intended—Cancer-Associated Fibroblasts and Vasculature Are Potential Targets in Cancer Therapy

Abstract: After oncogenic transformation, tumor cells rewire their metabolism to obtain sufficient energy and biochemical building blocks for cell proliferation, even under hypoxic conditions. Glucose and glutamine become their major limiting nutritional demands. Instead of being autonomous, tumor cells change their immediate environment not only by their metabolites but also by mediators, such as juxtacrine cell contacts, chemokines and other cytokines. Thus, the tumor cells shape their microenvironment as well as indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 390 publications
(514 reference statements)
0
31
0
Order By: Relevance
“…TAFs are important factors in tumor growth and VM formation [73][74][75]. Some studies have demonstrated that TAFs are required for tumor vascularization via various signaling pathways in malignant tumors [76][77][78]. In 2016, Yang et al showed that the conditioned medium of tumor-associated fibroblasts (CM-TAMs) could promote VM formation in vitro through secreting TGF-β and SDF1, and the expression of VE-cadherin, MMP-2, and laminin5γ2 was increased by TGF-β and SDF1 in hepatocellular carcinoma [73].…”
Section: Tumor-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…TAFs are important factors in tumor growth and VM formation [73][74][75]. Some studies have demonstrated that TAFs are required for tumor vascularization via various signaling pathways in malignant tumors [76][77][78]. In 2016, Yang et al showed that the conditioned medium of tumor-associated fibroblasts (CM-TAMs) could promote VM formation in vitro through secreting TGF-β and SDF1, and the expression of VE-cadherin, MMP-2, and laminin5γ2 was increased by TGF-β and SDF1 in hepatocellular carcinoma [73].…”
Section: Tumor-associated Fibroblastsmentioning
confidence: 99%
“…Furthermore, CSCs also play a significant role in the design of novel anti-tumor therapies [11][12][13]. The latest findings reveal that lncRNAs such as LINC00339, LINC00312, and MALAT1 could also be promising targets in anti-VM therapy [16,26,77]. Therefore, the clinical application of therapeutic strategies by targeting tumor VM needs further investigation in the future.…”
Section: Clinical Significance Of Vm In Cancermentioning
confidence: 99%
“…Previous studies has proved that angiogenesis can be weakened by inhibiting CAF-secreted cytokines and microvessels in the tumor can be normalized to increase micelles penetration. 69,70 On this basis, highly enhanced micelle retention was observed in TC therapy ( Figure 6), which was thought to correspond to IFP reduction and microvessels normalization. The control and tranilast groups also showed high radiant efficiency for remarkable EPR effect in breast cancer as a result of high vascular density.…”
Section: Discussionmentioning
confidence: 86%
“…Orchestrating TC survival and progression, the tumor microenvironment (TME) is characterized by the biochemical composition and biophysical properties of the extracellular matrix (ECM) by ECM-sequestered cytokines, as well as by the mutual interactions of the different cellular components, such as TCs, cancer-associated fibroblasts, immune cells, and ECs [ 20 , 21 ]. Within the TME, all these cells communicate through several juxtacrine and paracrine mechanisms.…”
Section: Introductionmentioning
confidence: 99%